Pengaruh Variasi Kecepatan Pengadukan Terhadap Hasil Pada Pembuatan Asam Oksalat Dari Bahan Dasar Ampas Tebu - Nababan, Febrina; Zultiniar, Zultiniar; Herman, Syamsu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Bagasse is a waste from the processing of sugar cane into sugar. The growing number of bagasse quantitatively into environmental problems that require attention and special handling. Bagasse contains cellulose, hemicellulose and lignin. Cellulose which contained in bagasse can be processed into useful products as oxalic acid by smelting with sodium hydroxide. Oxalic acid manufacturing process started from bagasse smelting mesh size of 40 by 15 grams with NaOH 4N for 75 minutes with a melting temperature of 180 Â°C and a long time stirring 20 minutes with stirring speed variations were 300, 400, 500 and 600 rpm. This research showed that 4.333 % yield of oxalic acid was produced at 600 rpm. Also, it indicated the stirring speed did not influence the oxalic acid yield. Keywords: Bagasse, cellulose, oxalic acid, sulfate acid, sodium hydroxide